Observational study of selective screening for prediabetes and diabetes in a real-world setting: an interprofessional collaboration method between public dental services and primary health care in Sweden - Harcke, Katri; Lindunger, Anders; Kollinius, Erik; Gebreslassie, Mihretab; Ugarph Morawski, Anna; Nylén, Charlotta; Peterson, Magnus; Yucel-Lindberg, Tülay; Östenson, Claes-Göran; Skott, Pia; Saleh Stattin, Nouha (Scandinavian journal of primary health care, 2024)
Describe a method in a real-world setting to identify persons with undiagnosed prediabetes and type 2 diabetes through an interprofessional collaboration between Public Dental Services and Primary Health Care in Regions Stockholm. A descriptive observational study. The study was conducted at seven sites in the region of Stockholm, Sweden. Each collaborating site consisted of a primary health clinic and dental clinic. Study participants included adults over 18 years of age who visited the Public Dental Services and did not have a medical history of prediabetes or type 2 diabetes. Selective screening is conducted in accordance with a risk assessment protocol at the Public Dental Services. In the investigated method, DentDi (Dental and Diabetes), adults diagnosed with caries and/or periodontitis over a cut-off value are referred to the Primary Health Care clinic for screening of prediabetes and type 2 diabetes. DentDi, introduced at seven sites, between the years 2017 and 2020, all of which continue to use the method today. A total of 863 participants from the Public Dental Services were referred to the Primary Health Care. Of those 396 accepted the invitation to undergo screening at the primary health care centre. Twenty-four individuals did not meet the inclusion criteria, resulting in a total of 372 persons being included in the study. Among the 372 participants, 27% (101) had elevated glucose levels, of which 12 were diagnosed with type 2 diabetes and 89 with prediabetes according to the study classification. DentDi is a feasible method of interprofessional collaboration where each profession contributes with the competence included in everyday clinical practice for early identification of persons with prediabetes and type 2 diabetes with a complete chain of care. The goal is to disseminate this method throughout Stockholm County and even other regions in Sweden.